Effect of dispersing CTBN into Diglycidyl Ether of Bisphenol-A on Mixed mode Loading. Issue 1 (March 2021) - Kumar, PJ.V. Sairasanna; Baskar, S.
Abstract: Delamination of polymer composite is one of the major failure characteristic, in this context the fracture behavior of the tailored composites in combination of opening mode and shearing mode is assessed and its fracture robustness of the glass fiber reinforced laminate are determined experimentally, in this present work by developing a modified Arcan fixture using a single edge notched specimen for characterizing in various loading conditions, The fixture was made of industrial grade Aluminum ingot machined to an outer diameter of 150 mm, having a thickness of 10 mm. The fixture had provision to load the sample at different oblique angles up to 90 degrees in steps of 15 degrees. The samples were attached to the fixture by means of fasteners and were tested in tensile mode using a 40 KN Instron tensile tester at constant displacement and ambient conditions. Further, the resin was strengthened with Carboxyl Terminated Butadiene Arenonitrile (CTBN) and its effect on fracture parameters was studied by varying the loading angles. Results indicate that the fracture parameters vary with loading and at angles greater than 45 degrees, the GFRP sample's behavior changes from opening mode to shearing mode and the converse is also true. This pattern is similar, with the specimens even after modifying the resin with CTBN however, it was found that stress intensity factor increased corresponding to the increase of CTBN infusion. CTBN was dispersed into the Bisphenol base A (LY566– A general purpose thermoset epoxy resin) in three different percent: 1%, 3% and 5% by weight. The layup sequence used in this work was cross ply. The effect of varying the loading angles on the stress intensity factors were studied.